Electronic and Chemical Properties of Donor, Acceptor Centers in Graphene - Telychko, Mykola; Mutombo, Pingo; Merino, Pablo; Hapala, Prokop; Ondráček, Martin; Bocquet, François C; Sforzini, Jessica; Stetsovych, Oleksandr; Vondráček, Martin; Jelínek, Pavel; Švec, Martin (ACS nano, 2015)
Chemical doping is one of the most suitable ways of tuning the electronic properties of graphene and a promising candidate for a band gap opening. In this work we report a reliable and tunable method for preparation of high-quality boron and nitrogen co-doped graphene on silicon carbide substrate. We combine experimental (dAFM, STM, XPS, NEXAFS) and theoretical (total energy DFT and simulated STM) studies to analyze the structural, chemical, and electronic properties of the single-atom substitutional dopants in graphene. We show that chemical identification of boron and nitrogen substitutional defects can be achieved in the STM channel due to the quantum interference effect, arising due to the specific electronic structure of nitrogen dopant sites. Chemical reactivity of single boron and nitrogen dopants is analyzed using force-distance spectroscopy by means of dAFM.
Keywords: chemical reactivity; boron; graphene; doping; nitrogen